Ethical Dimensions of Capacity-Building for Community Engagement: A Study of Ward Committee Members in Johannesburg’s Ward 68 - Mdhlalose, Dickson Scotch; Hlungwana, Jabulani (FISIP UIN Sunan Gunung Djati Bandung, 2025)
Research Problem: Ward Committees play a critical role in facilitating community engagement and participatory governance at the local level. However, in Johannesburg’s Ward 68, limited and inconsistent capacity-building initiatives raise ethical and moral concerns regarding accountability, trust, and inclusivity in local governance. Insufficient training and institutional support undermine the ability of Ward Committee members to engage communities effectively and ethically. Research Purposes: This study aims to examine capacity-building initiatives among Ward Committees in Ward 68 of the City of Johannesburg, with a particular focus on the ethical and moral dimensions of community engagement. Specifically, the study seeks to identify ways to enhance the skills, knowledge, and ethical competencies required by Ward Committee members to foster trust, accountability, and constructive relationships with local communities. Research Methods: The study adopts a qualitative research approach using semi-structured interviews. Primary data were collected through in-depth interviews with ten Ward Committee members, while secondary data were obtained from academic journals, government publications, and City of Johannesburg reports. The data were analysed thematically to identify recurring patterns and themes relevant to ethical governance and capacity-building. Results and Discussion: The findings reveal that the City of Johannesburg primarily provided induction training for Ward Committees, with limited follow-up or continuous capacity-building. Some members were unable to attend the training due to various constraints, while others attended but could not recall its content. These limitations, alongside broader structural and operational challenges, weakened the ethical effectiveness of Ward Committees, particularly in promoting inclusive participation, accountability, and trust in community engagement. Research Implications and Contributions: This study contributes empirical insights into the ethical challenges affecting capacity-building in Ward Committees within a metropolitan governance context. It highlights the need for ethically informed, ward-specific training programmes, clearer role definitions, improved remuneration, and equitable representation policies. By foregrounding the moral dimensions of participatory governance, the study offers practical and theoretical contributions to debates on ethical public policy and local governance in South Africa.